Zolazepam-tiletamine-medetomidine versus butorphanol-azaperone-medetomidine for the immobilisation of captive leopards (Panthera pardus) - Buck, Roxanne Kate (University of Pretoria, 2024)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2021.